The Visualisation of Polyadic Sustained Shared Thinking Interactions: A Methodological Approach - Waibel, Alexandra (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2021)
Sustained shared thinking (SST) is considered an important element of high-quality teacher child interaction (SIRAJ-BLATCHFORD, SYLVA, MUTTOCK, GILDEN & BELL, 2002). However, SST rarely occurs in early childhood institutions, and when it is studied, it is mainly observed in dyadic interactions. Since communication in kindergarten also takes place in group settings, polyadic SST-dialogues were explored in this study using videography, information about children's family language (monolingual/multilingual) and tests for children on emergent literacy from the international research project "SpriKiDS" (VOGT et al., 2019). Micro-processes were analysed by means of linguistic conversation analysis (BRINKER & SAGER, 2010) and grounded theory method (STRAUSS & CORBIN, 1996 [1990]) to identify strategies that promote SST in groups of children. Within the analysis process, visualisations were developed to discover elements of polyadic SST-interactions and to present findings. In this article, possibilities and limitations of visualisations for analysis and presentation purposes are described by means of two play sequences in different group sizes. The use of visualisations seems to support the exploration of teachers' interaction strategies and helps to discover patterns by putting an analytical lens on micro-processes around children's SST-contributions. An added value is seen in the graphic display of complex relationships, which can contribute to the understanding in presentations.